2022
DOI: 10.3389/fmicb.2022.908845
|View full text |Cite
|
Sign up to set email alerts
|

Human milk microbial species are associated with infant head-circumference during early and late lactation in Guatemalan mother-infant dyads

Abstract: Human milk contains abundant commensal bacteria that colonize and establish the infant’s gut microbiome but the association between the milk microbiome and head circumference during infancy has not been explored. For this cross-sectional study, head-circumference-for-age-z-scores (HCAZ) of vaginally delivered breastfed infants were collected from 62 unrelated Mam-Mayan mothers living in eight remote rural communities in the Western Highlands of Guatemala during two stages of lactation, ‘early’ (6–46 days postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 128 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…A limited number of studies had previously reported associations between maternal nutrient intakes during lactation that had uncovered both multiple positive and negative associations with the HMM at the phylum and genus levels using correlation and cluster analyses ( 23 26 ). Since associations between the HMM and maternal nutrient intakes with infant growth parameters had not been explored, we also investigated associations of maternal nutrient intakes with previously established DA species that differed between infants with ‘normal infant z-scores’ defined as WAZ ≥ −1SD, LAZ ≥ 1.5SD, and HCAZ ≥ −1SD compared with infants experiencing growth faltering defined as mildly underweight (WAZ < −1SD), mildly stunted (LAZ < −1.5SD), and with smaller head circumferences (HCAZ < −1SD) by the stage of lactation ( 44 , 45 ). Moreover, given that human milk continuously provides an infant with a dynamically changing community of commensal and potentially beneficial bacteria that differs between early and late lactation ( 43 ), we conducted our analyses at the species level during both early and late lactation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited number of studies had previously reported associations between maternal nutrient intakes during lactation that had uncovered both multiple positive and negative associations with the HMM at the phylum and genus levels using correlation and cluster analyses ( 23 26 ). Since associations between the HMM and maternal nutrient intakes with infant growth parameters had not been explored, we also investigated associations of maternal nutrient intakes with previously established DA species that differed between infants with ‘normal infant z-scores’ defined as WAZ ≥ −1SD, LAZ ≥ 1.5SD, and HCAZ ≥ −1SD compared with infants experiencing growth faltering defined as mildly underweight (WAZ < −1SD), mildly stunted (LAZ < −1.5SD), and with smaller head circumferences (HCAZ < −1SD) by the stage of lactation ( 44 , 45 ). Moreover, given that human milk continuously provides an infant with a dynamically changing community of commensal and potentially beneficial bacteria that differs between early and late lactation ( 43 ), we conducted our analyses at the species level during both early and late lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported differences in the HMM between infants with normal growth and infants with mild growth faltering ( 44 , 45 ). We identified 30 differentially abundant (DA) taxa between the LAZ groups [mildly stunted (LAZ < −1.5SD) versus the non-stunted (LAZ ≥ −1.5SD)], 23 DA taxa between the WAZ groups [normal weight (WAZ ≥ −1SD) versus the mildly underweight (WAZ < −1SD)], and 26 DA taxa were identified between HCAZ groups [normal HC (HCAZ ≥ −1 SD) versus the smaller HC (HCAZ < −1 SD)] ( 44 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cross-sectional study was carried out to examine the correlation between the milk microbiome and neurodevelopment, specifically focusing on head circumference-for-age z-scores (HCAZ) in breastfed infants [ 110 ]. Significant differences in the milk microbiota composition were found between infants with HCAZ ≥ −1 SD and HCAZ < −1 SD at both early (≤46 days postpartum) and late stages of lactation (109–184 days postpartum).…”
Section: Microbiomementioning
confidence: 99%
“…The HCAZ ≥ −1 SD group had a higher abundance of Streptococcus species associated with human milk, while the HCAZ < −1 SD group, particularly at the late stage of lactation, exhibited a higher abundance of differentially abundant taxa associated with environmentally and potentially opportunistic species. These findings suggest a potential association between the milk microbiome and brain growth in breastfed infants during lactation, necessitating, however, further investigation into the interplay between the human milk microbiome and infant neurodevelopment [ 110 ].…”
Section: Microbiomementioning
confidence: 99%